Anti-inflammatory cyclohexenyl chalcone derivatives in Boesenbergia pandurata - Patoomratana Tuchinda (2018)
The cyclohexenyl chalcone derivative [(-)-hydroxypanduratin A], together with the previously known panduratin A, sakuranetin, pinostrobin, pinocembrin, and dihydro-5,6-dehydrokawain were isolated from the chloroform extract of the red rhizome variety of Boesenbergia pandurata (Robx.) Schltr. [currently known as Boesenbergia rotunda (L.) Mansf., Kulturpfl.]. Their structures were assigned on the basis of their spectroscopic data. (-)-Hydroxypanduratin A and (-)-panduratin A showed significant topical anti-inflammatory activity in the assay of TPA-induced ear edema in rats. © 2002 Elsevier Science Ltd. All rights reserved.